The Effect of Financial Literacy and Financial Management on Financial Well-being in MSMEs Medan Helvetia District - Jane Gloria Shieh; Putri Wahyuni; Albert herlambang (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to analyze the effect of financial literacy and financial management on financial well-being in Micro, Small, and Medium Enterprises (MSMEs) in Medan Helvetia District. This study uses a quantitative approach method and primary data, where the research data is in the form of survey results on MSMEs in Medan Helvetia District and uses a saturated sample of 60 samples. Data analysis and testing consist of validity tests, reliability tests, descriptive statistics, classical assumption tests, multiple regression analysis, partial hypothesis testing (t test) and simultaneous (F test). The results of the validity and reliability tests indicate that the research instrument is valid and reliable. The results of this study indicate that financial literacy has a significant effect on the financial well-being of MSMEs in Medan Helvetia District with a calculated t value of 3.927 > t table 2.00172. Financial management has a significant effect on the financial well-being of MSMEs in Medan Helvetia District with a calculated t value of 2.250 > t table 2.00172. Financial literacy and financial management have a significant simultaneous effect on the financial well-being of MSMEs in Medan Helvetia District with a calculated F value of 16.326 > F table 3.16. The coefficient of determination (R2) value of 0.363 indicates that 36.3% of the variation in financial well-being can be explained by financial literacy and financial management, while the remaining 63.7% is explained by other factors outside this research model.